Evaluation Of Anti Dermatophyte Activity Of Crude Lawsone Isolated From Lawsonia Inermis Leaves (Journal of Pharmaceutical Negative Results, 2022)
Dermatophytes are a group of filamentous fungi that cause infections of the skin .The various diseases caused by dermatophytes include athlete's foot, ringworm, jock itch, and nail infections (onychomycosis). Lawsonia inermis commonly called as henna and its leaves, flower, seeds, stem bark, roots have been found to exhibit antioxidant, antidiabetic, hepatoprotective, hypoglycemic, antimicrobial, anticancer and wound healing properties while Lawsone the naphtha quinone present in Lawsonia inermis leaves were reported to possess antifungal, antibacterial, bruises, skin disorders, amoebiasis, burns and bruises and leprosy. Lawsone was isolated from the aerial parts of L.inermis and quantified using HPTLC technique. The anti dermatophyte activity of the isolated lawsone was carried out by using Cup and Plate method and Poisoned plate method in dermatophytes viz. Trichophyton mentagraphyte and Trichophyton rubrum in the concentrations of 31.25, 62.5, 125, 250, 500 and 1000 µg/ml concentration. The minimum inhibitory concentration of lawsone was calculated by broth dilution assay method and found to be 500 µg/ml for both the dermatophytes and the percentage inhibition was found to be significant against T.mentagraphytes, 72.5% and 83.41% against T.rubrum when compared to fluconozole standard (96.74% and 98.42% respectively). From the results it was concluded that lawsone may be an effective phyto constituent responsible for anti dermatophyte activity.